2004
DOI: 10.1542/peds.2004-1073
|View full text |Cite|
|
Sign up to set email alerts
|

Hypotensive Extremely Low Birth Weight Infants Have Reduced Cerebral Blood Flow

Abstract: In ELBW infants (1) cerebral autoregulation is functional in normotensive but not hypotensive infants; (2) a breakpoint exists at approximately 30 mm Hg in the CBF-MAP autoregulation curve; and (3) dopamine improves both MAP and CBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
190
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(206 citation statements)
references
References 33 publications
9
190
3
3
Order By: Relevance
“…During the first postnatal day, this number is generally considered to be equal to the numerical number of the given patient's gestational age. However, most [2][3][4] but not all 5 studies using 133 Xe clearance or near infrared spectroscopy (NIRS) to assess changes in cerebral blood flow (CBF) have found that the lower limit of the autoregulatory blood pressure range may be around 30 mm Hg even in the 1-day-old extremely low birth weight (ELBW) neonate. These findings are supported by observations made by the use of ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the first postnatal day, this number is generally considered to be equal to the numerical number of the given patient's gestational age. However, most [2][3][4] but not all 5 studies using 133 Xe clearance or near infrared spectroscopy (NIRS) to assess changes in cerebral blood flow (CBF) have found that the lower limit of the autoregulatory blood pressure range may be around 30 mm Hg even in the 1-day-old extremely low birth weight (ELBW) neonate. These findings are supported by observations made by the use of ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,9,22 Management of this presentation of circulatory compromise is difficult and findings in the literature are somewhat contradictory. In a well-executed series using SVC blood flow as a surrogate measure of CBF in VLBW neonates during the first postnatal day, Evans, Kluckow, Osborn and colleagues described the hemodynamics of systemic and cerebral hypoperfusion, 7,8 the relationship between recovery from hypoperfusion and the development of IVH, 8 the weak relationship between SVC blood flow and systemic blood pressure 8 and the association between neurodevelopmental outcome at 3 years of age and low SVC blood flow during the first 24 postnatal hours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not know the mean arterial blood pressure value at which cerebrovascular autoregulation is lost in the preterm infant, although recent studies suggest that it may be as high as 28 to 30 mm Hg in even extremely low birth weight infants ( Figure 2). 22 There is an association between the loss of autoregulation, the resultant CBF fluctuations, and morbidity and mortality in preterm infants. 12,16,21 However, according to the physiological model (Figure 1), cerebral cellular function and structural integrity are not affected at the autoregulatory threshold, and association does not imply causation.…”
Section: Definition Of Hypotensionmentioning
confidence: 99%